2016
DOI: 10.9789/2175-5361.2016.v8i4.5054-5061
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento de estudantes adolescentes sobre transmissão, prevenção e comportamentos de risco em relação às DST/HIV/AIDS Adolescent students knowledge about transmition, prevention and risky behavior related to STD/HIV/AIDS

Abstract: Objetivo: Avaliar o conhecimento dos adolescentes sobre sexualidade, métodos contraceptivos e doenças sexualmente transmissíveis, assim como analisar a vulnerabilidade e comportamentos de risco destes em relação as DST/aids. Métodos: Estudo descritivo-exploratório com abordagem quantitativa realizado de março a dezembro de 2013 com 222 estudantes da rede pública de ensino. Os dados foram coletados a partir de um questionário semiestruturado respondido em sala de aula. Resultados: O estudo apontou índices signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 6 publications
(8 reference statements)
0
1
0
1
Order By: Relevance
“…15 It was identified that 6.56% of the videos spoke about this parameter and it should be remembered that these aspects are also related to vulnerability, since they were verified in an integrative review as: knowledge, behavior and its conditioning factors, as well perceptions of the vulnerability of adolescents with HIV / AIDS that, according to the current literature, may also cover other contexts. 16 In relation to the family relationship, it was found that the videos watched represented 3.03% of the total and reported, in their content, the difficulty that individuals had when talking to their relatives, since they were afraid of the judgment and of discrimination. It is noticed, however, that some said that the family stayed close by offering the necessary support.…”
Section: Discussionmentioning
confidence: 99%
“…15 It was identified that 6.56% of the videos spoke about this parameter and it should be remembered that these aspects are also related to vulnerability, since they were verified in an integrative review as: knowledge, behavior and its conditioning factors, as well perceptions of the vulnerability of adolescents with HIV / AIDS that, according to the current literature, may also cover other contexts. 16 In relation to the family relationship, it was found that the videos watched represented 3.03% of the total and reported, in their content, the difficulty that individuals had when talking to their relatives, since they were afraid of the judgment and of discrimination. It is noticed, however, that some said that the family stayed close by offering the necessary support.…”
Section: Discussionmentioning
confidence: 99%
“…Aí assim, mas eu não culpo também ninguém. (Arthur, 25 anos, diagnosticado há 1 ano) O abuso de álcool e outras drogas está relacionado ao uso inconsistente de preservativo e é citado como fator de vulnerabilidade ao HIV/aids e outras ISTs em diversos estudos (Nelson et al, 2016;Pereira et al, 2012). As conclusões dos estudos indicam a necessidade do incremento de estratégias de redução de danos, como o incentivo da autorresponsabilidade e autoproteção dos jovens, o que aponta para o aspecto da retórica do sexo com responsabilidade na esfera da prevenção.…”
Section: Vidas Que Seguem: Ditos E Não Ditos Sobre O Viver Com Hiv/aidsunclassified